PHARMACOKINETICS OF CINOXACIN IN PATIENTS WITH IMPAIRED RENAL FUNCTION - OHKAWA, MITSUO; SUGATA, TOSHIAKI; KURODA, KYOICHI; OKASHO, AKIRA; SAWAKI, MASARU; KAWAGUCHI, KOHEI; TAKANO, MANABU (CHEMOTHERAPY, 1980)
The pharmacokinetics of cinoxacin, a new synthetic antibacterial agent, were examined in 6 healthy volunteers and 12 patients with different endogeneous creatinine clearances (Ccr) on the basis of a one-compartment open model. Each subject received a single 400mg oral dose of cinoxacin, and serum and urinary concentrations of free cinoxacin and cinoxacin conjugate were measured by a fluorometric method. The mean peak concentration of free cinoxacin in serum was achieved 3 hours after administration in normal subjects. The mean serum half-life of free cinoxacin was calculated for 66 minutes in normal subjects, and increased in patients along with increasing impairment of renal function. A significant correlation between the elimination rate constant and Ccr was demonstrated (p<0.001). In normal subjects, 62% of the drug was excreted in the urine as free cinoxacin within the first 12 hours, 95% as total cinoxacin including cinoxacin conjugate. The urinary excretion rate declined gradually in patients as a degree of renal impairment advanced.